BIM and the Art of Motorcycle Maintenance. Issue 4 (2nd October 2018) - Knight, Martin
Abstract: Storytelling is a form of communication with which the best designers are intimately familiar; their ability to weave a tale about their designs is as strong as (and sometimes even stronger than) their ability to produce excellent designs. The powerful relationship between words and images can animate a project and allow it to be understood by the most diverse audience—but this age-old tradition is under threat from social media and other contemporary modes of communication. Using themes from Robert Pirsig's Zen and the Art of Motorcycle Maintenance, this paper explores the relationship between the use of building information modelling (BIM) and the communication of bridge design.